1999
DOI: 10.1074/jbc.274.24.16953
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evidence for Heme Linkage through Esters with Asp-93 and Glu-241 in Human Eosinophil Peroxidase

Abstract: The covalent heme attachment has been extensively studied by spectroscopic methods in myeloperoxidase and lactoperoxidase (LPO) but not in eosinophil peroxidase (EPO). We show that heme linkage to the heavy chain is invariably present, whereas heme linkage to the light chain of EPO is present in less than one-third of EPO molecules. By sequence analysis of isolated heme peptides after aminolysis, we unambiguously identified the acidic residues, Asp-93 of the light chain and Glu-241 of the heavy chain, that for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 37 publications
3
47
0
Order By: Relevance
“…In contrast, recent work from this laboratory has demonstrated that the covalent bonds in lactoperoxidase are formed via an autocatalytic process when the noncovalent heme-protein complex reacts with H 2 O 2 (6,7). Evidence that similar autocatalytic processes mediate covalent attachment of the heme groups in the eosinophil and thyroid peroxidases has subsequently been reported (8,9).…”
mentioning
confidence: 87%
“…In contrast, recent work from this laboratory has demonstrated that the covalent bonds in lactoperoxidase are formed via an autocatalytic process when the noncovalent heme-protein complex reacts with H 2 O 2 (6,7). Evidence that similar autocatalytic processes mediate covalent attachment of the heme groups in the eosinophil and thyroid peroxidases has subsequently been reported (8,9).…”
mentioning
confidence: 87%
“…Spectra were externally calibrated using four identified molecular ions of a standard peptide mixture, yielding an accuracy of 0.01-0.05%. Non-heme peptides were observed as MH ϩ species, but heme peptides were observed as M ϩ species as described previously for lactoperoxidase and eosinophil peroxidase heme peptides (32). The intact heme peptides were observed along with the free peptides resulting from cleavage of the peptide-heme linkage in the instrument.…”
Section: Isolation and Characterization Of Heme-containingmentioning
confidence: 98%
“…The heme group has been shown to be cross-linked to the protein in lactoperoxidase (27,28), myeloperoxidase (29 -31), eosinophil peroxidase (32), and thyroid peroxidase (33). The heme prosthetic group in lactoperoxidase, the only one that has been fully characterized, is iron 1,5-bis(hydroxymethyl)-3,8-dimethyl-2,4-divinylporphyrin-6,7-dipropionic acid.…”
Section: Fig 5 Comparison Of Lc Analysis Of Cyp4a1 Before (A) and Amentioning
confidence: 99%
“…We established earlier that the prosthetic group is bound to the protein in LPO via a self-activating process in which noncovalently bound heme becomes covalently bound on exposure of the heme-protein complex to H 2 O 2 (4). Recent evidence indicates that a similar mechanism is involved in covalent attachment of the heme to the protein in EPO and thyroid peroxidase (12,13).…”
Section: Lpomentioning
confidence: 99%